Analisa Sistem Aplikasi Marketplace Facebook Dalam Pengembangan Dunia Bisnis - Joko Riyanto; Supriyanto Supriyanto (STMIK Budi Darma, 2020)
Trade in the modern era currently uses a system of buying and selling not directly face-to-face but only with one finger and in one right is not limited by space and time which is commonly called online trading and online transactions in one place, namely the website and there are very many types of marketplaces as long as technology continues to develop and changes in the quality of technology continue, in this study the author wants to show the use of the Facebook marketplace in the business world, showing an increase in economic growth for every group and age by utilizing technology provided by Facebook, the results of This research shows the quality of the selection of the Facebook marketplace as a site that is quite busy being used by many people today as the most accessible and friendlier marketplace.